2017
DOI: 10.20287/ec.n25.v1.a11
|View full text |Cite
|
Sign up to set email alerts
|

Audiências e cross-media: estudo de padrões de consumo de notícias em Portugal

Abstract: ResumoAs práticas digitais que decorrem da ubiquidade dos media e da sua utilização possibilitaram a combinação de múltiplas plataformas no consumo de notí-cias. Neste artigo, procurámos identificar repertó-rios mediáticos (padrões de uso dos media noticiosos) em Portugal, de modo a compreender como são construídas as preferências mediáticas das audiên-cias e de que forma o consumo noticioso integra os seus hábitos quotidianos. Neste sentido, desenvolvemos uma análise a padrões de consumo de media noticiosos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…The Portuguese media managed, over the years, to separate themselves from an ideological and party culture, becoming more professional than several countries, namely in southern Europe [77][78][79]. da Silva et al (2017) characterize the Portuguese media system as being hybrid and complex, composed of public and private media, with detachment from political control [79].…”
Section: Portuguese Casementioning
confidence: 99%
See 1 more Smart Citation
“…The Portuguese media managed, over the years, to separate themselves from an ideological and party culture, becoming more professional than several countries, namely in southern Europe [77][78][79]. da Silva et al (2017) characterize the Portuguese media system as being hybrid and complex, composed of public and private media, with detachment from political control [79].…”
Section: Portuguese Casementioning
confidence: 99%
“…The Portuguese media managed, over the years, to separate themselves from an ideological and party culture, becoming more professional than several countries, namely in southern Europe [77][78][79]. da Silva et al (2017) characterize the Portuguese media system as being hybrid and complex, composed of public and private media, with detachment from political control [79]. The Portuguese government has been led by moderate parties (center-left-Socialist Party (PS) and center-right-Social Democratic Party (PSD)) with the exception of some coalitions with the Social Democratic Center (CDS), a right-wing conservative party, without the representation of extremist ideals [80,81].…”
Section: Portuguese Casementioning
confidence: 99%
“…Contudo, e balizando o nosso argumento, a confiança em notícias por parte dos portugueses ficará fundamentalmente a dever-se à confiança dos públicos de notícias relativamente aos jornalistas portugueses e ao seu trabalho. Como referem Silva et al (2017aSilva et al ( , 2017b, os públicos de notícias em Portugal têm uma perceção francamente positiva dos jornalistas e dos media credenciados em termos da sua credibilidade, confiança e papel na democracia, uma vez que estudos qualitativos sobre o consumo de media em Portugal, segundo os autores, concluem que os portugueses preferem as ideias normativas de produção de notícias características do jornalismo profissional exercido em organizações de media reputadas.…”
Section: Discussionunclassified
“…Fourthly, the public's perceptions of journalists and the media is highly positive in terms of credibility, trust and role in democracy. In fact, recent qualitative studies of media consumer practices in Portugal have concluded that users "prefer normative and institutional ideas of news produced by journalistic professionals and in which the media organisation's reputation stands out as an important criterion in the majority of media repertories" (Silva et al, 2017a(Silva et al, , 2017b. This may also be linked to the high levels of trust in the news in Portugal.…”
Section: Discussionmentioning
confidence: 99%